1973
DOI: 10.1042/bj1340629
|View full text |Cite
|
Sign up to set email alerts
|

Determination and significance of l-tyrosine O-sulphate and its deaminated metabolites in normal human and mouse urine

Abstract: Methods were developed for the determination of the O-sulphate esters of l-tyrosine, p-hydroxyphenylpyruvate, p-hydroxyphenylacetate and p-hydroxybenzaldehyde in human urine. The amounts of these esters normally present in human female urine were determined. The quantities and specific radioactivities of l-tyrosine O-sulphate and p-hydroxyphenylpyruvate O-sulphate in mouse urine after labelled tyrosine had been fed were determined and were consistent with the hypothesis that the sole source of p-hydroxyphenylp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…Similar findings were made subsequently for other mammalian species including rat, rabbit, and mouse (5,6). Because none of the mammalian arylsulfatases could effectively catalyze its desulfation (7,8), the free TyrS produced by mammalian cells has been generally considered a modified amino acid destined to be excreted.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Similar findings were made subsequently for other mammalian species including rat, rabbit, and mouse (5,6). Because none of the mammalian arylsulfatases could effectively catalyze its desulfation (7,8), the free TyrS produced by mammalian cells has been generally considered a modified amino acid destined to be excreted.…”
supporting
confidence: 58%
“…This enzyme, however, cannot catalyze the sulfation of unmodified L-tyrosine (13). In view of the widespread occurrence of the post-translational tyrosine sulfation among proteins of multicellular eukaryotic organisms (14), it has become increasingly accepted that the free TyrS excreted in mammalian urine is probably derived exclusively from the degradation of tyrosine sulfated proteins (1,6,(15)(16)(17). In support of this hypothesis, free Tyr[ 35 S] was shown to be generated when tyrosine 35 S-sulfated peptides or proteins were either injected into rabbits (15) or added to the medium of cultured cells (18).…”
mentioning
confidence: 99%
“…They have been confirmed in P‐selectin glycoprotein ligand‐1 and in human chemokine receptors (CXCR3, CXCR4, CCR2b, CCR5, and CX3CR1) . Tyrosine sulfate also arises in part from the turnover of fibrinogen, which is a strong cardiovascular risk factor in the general population and other polypeptides . P‐selectin glycoprotein ligand‐1 is a mucin on leukocytes that interacts with P‐ and L‐selectin to support leukocyte rolling along the vascular wall.…”
Section: Discussionmentioning
confidence: 95%
“…In line with these results, other intervention studies with polyphenols and polyphenol‐rich foods, such as red wine, observed significant lower levels of CCR2 , but this parameter was not studied in the present intervention study. Therefore, the decrease of urinary tyrosine‐ O ‐sulfate in the CM group could come not only from one protein , but also from the overall decreased amounts of these O ‐sulfated‐containing polypeptides and other unknown proteins caused by the CM.…”
Section: Discussionmentioning
confidence: 99%
“…A great number of investigations have since been made to clarify the biochemical origin of the free TyrS excreted. Studies using various cell homogenates or purified aryl sulfotransferases, however, persistently failed to reveal the enzymic activity catalyzing the sulfation of L-tyrosine [4-81. Considering the widespread occurrence of the posttranslational tyrosine sulfation among proteins and peptides of multicellular eukaryotic organisms [9], it has been proposed that the free TyrS excreted in mammalian urines represents a degradation product of tyrosine-sulfated proteins [3,10,111. Indeed, free T Y~ [~~S ] was shown to be generated and released when tyr~sine-[~~S]sulfated peptides or proteins were either injected into rabbit [lo] or added to the medium of cultured cells 1121.…”
mentioning
confidence: 99%